Konec demokracije? - Lukšič, Andrej (Teorija in praksa, 2009)
The author raises the question of democracy in the context of a capitalist society. He shows democracy in several development phases which are the result of changing social and political power, knowing at the same time that capitalism can function without democracy. He links democracy with the rule of law and insists that the rule of law is a necessary condition of democracy, but democracy cannot be replaced by the rule of law. Persisting with this idea means paving the way for authoritarianism. He defines democracy by the relationship between the rulers and the ruled and points out that democracy is only one possible form of this relationship. The change of democracy in a capitalist society and its potential to slip into authoritarianism is linked with the activity of protagonists within the given and yet always changing structural and cultural conditions, which are the outcome of the previous activity of protagonists and the balance of power between them.
Keywords: Democracy; Demokracija; Kapitalizem; Capitalism; Political power; Politična moč; pravna država